An Overview of Social Anxiety in Young Girls at Senior High Schools in Sidoarjo: Gambaran Social Anxiety pada Remaja Putri di Sekolah Menengah Atas di Sidoarjo - Annisa, Widya; Mariyati, Lely Ika (Indonesian Journal of Innovation Studies, 2023)
This research is motivated by the phenomenon of adolescent girls experiencing social anxiety at SMA Porong Sidoarjo. This study uses a descriptive quantitative research method with data collection in this study using a Likert scale model, namely the social anxiety scale modified from the Adawiyah Robiah scale. The sample in this study were 233 young women from 683 populations. The results showed that young women had high social anxiety, there was a frequency of Social Anxiety Levels with the acquisition of a percentage of 38%, namely young women had high social anxiety and based on the aspect of obtaining 37% in the negative evaluation aspect.